(A Study on The Effect of Temperature, pH and Hidrolizing Time in The Extraction of Pectin from Passion Fruit Pericarp (Passiflora edulis sims). - Subardj SK; Siti Sofiah; Entjep Tarmidji; Juli Astuti (Balai Besar Industri Agro, 1989)
A study on the effect of temperature, pH and time in hydrolizing passion fruit pericarp to produce pectin has been conducted. The result showed that the application of variable temperature altered the amount of pectin obtained significantly. However there was no significant effect of using variable pH and time of hidrolization as well as their interactions on it. As much as 11,89% (d.b) of pectin was obtained at the hidrolization temperature of 100 C , which higher compared to that of the temperature of 60 C (9,85%) and of 80 C (10, 54%). Pectin obtained from the passion fruit pericarp extraction was categorized as a High Methoxyl Pectin which has the methoxyl content of more than 7%, with a jelly grade of 100 and a slow set characteristic that is setting time of about 3 minutes.